1987
DOI: 10.1073/pnas.84.9.3075
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom allele associations between unlinked protein loci: are the polymorphisms of the immunoglobulin constant regions adaptive?

Abstract: Consistent linkage disequilibrium was observed between independently segregating protein loci. In natural populations of the European rabbit Oryctolagus cuniculus, highly significant, nonrandom associations between alleles of the constant regions of the immunoglobulin light and heavy chains were found, both within localities and between localities. We suggest that the population genetic data presented here are relevant to the adaptive significance of the genetic polymorphisms of the antibody constant regions.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The subsequent colonization of the rest of continental Europe happened during the Middle Ages, and the analysis of protein polymorphism , immunoglobulin allotypes (van der Loo et al 1987Loo et al , 2001 and mtDNA diversity in both extant and extinct populations (Hardy et al 1995) indicate that this process was a mixture of a geographical expansion promoted by human-induced habitat changes together with the emergence of domestic breeds and the release of animals of mixed origin for hunting purposes (Callou 2003). Disentangling between the two processes is extremely difficult because rabbit domestication likely took place in southern France at approximately the same time (Callou 2003), but the future use of markers that are informative between ancestral wild populations and present-day breeds will certainly help to address this question.…”
Section: What Can We Infer About the Geographical Expansion Of The Ramentioning
confidence: 97%
“…The subsequent colonization of the rest of continental Europe happened during the Middle Ages, and the analysis of protein polymorphism , immunoglobulin allotypes (van der Loo et al 1987Loo et al , 2001 and mtDNA diversity in both extant and extinct populations (Hardy et al 1995) indicate that this process was a mixture of a geographical expansion promoted by human-induced habitat changes together with the emergence of domestic breeds and the release of animals of mixed origin for hunting purposes (Callou 2003). Disentangling between the two processes is extremely difficult because rabbit domestication likely took place in southern France at approximately the same time (Callou 2003), but the future use of markers that are informative between ancestral wild populations and present-day breeds will certainly help to address this question.…”
Section: What Can We Infer About the Geographical Expansion Of The Ramentioning
confidence: 97%
“…The first relevant data came from the analysis of the so-called immunoglobulin allotypes (Mage et al 1973). The study of the IgKC1 and IgVH1 loci revealed a remarkable contrast between the high levels of diversity found in rabbits from the Iberian Peninsula and the homogeneity of other European populations, including very similar domestic breeds (Cazenave et al 1987;van der Loo 1987;van der Loo et al 1987van der Loo et al , 1991. However, a coherent picture of the evolutionary history of the rabbit started to emerge only a few years later, with the work of Biju- Duval et al (1991) based on the analysis of mtDNA.…”
Section: Genetic Structure Of Wild Rabbit Populationsmentioning
confidence: 99%
“…They are also the target of pathogens (Kim et al . 1999), and different lines of evidence suggest that genetic variation in this region is adaptive (van der Loo et al . 1987, 1996).…”
Section: Correspondence Of Rabbit Ighgch2 Allotypes Wimentioning
confidence: 99%